2021
DOI: 10.1007/s00167-021-06703-8
|View full text |Cite
|
Sign up to set email alerts
|

ACL graft with extra-cortical fixation rotates around the femoral tunnel aperture during knee flexion

Abstract: Purpose An understanding of the behavior of a new ACL graft in the femoral tunnel during knee motion and external loading can provide information pertinent to graft healing, tunnel enlargement, and graft failure. The purpose of the study was to measure the percentage of the tunnel illed by the graft and determine the amount and location of the graft-tunnel contact with knee motion and under external knee loads. Methods Single bundle anatomical ACL reconstruction was performed on six cadaveric knees. Specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…It has been reported that during knee joint flexion and extension, the force exerted on the graft mainly produces two effects, namely the “bungee effect” and “windshield-wiper effect” [ 41 ]. The former is described as the longitudinal movement of the implant in the bone tunnel after ACLR, while the latter is a transverse movement relative to the bone tunnel [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that during knee joint flexion and extension, the force exerted on the graft mainly produces two effects, namely the “bungee effect” and “windshield-wiper effect” [ 41 ]. The former is described as the longitudinal movement of the implant in the bone tunnel after ACLR, while the latter is a transverse movement relative to the bone tunnel [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that the ultimate failure load of graft was reduced by approximately 25% due to graft laceration by the interference screw 28 . Suspensory fixation allows for circumferential tendon‐bone contact, but its fixation point far away from the joint line can produce a “bungee effect” and a “windshield wiper effect” with cyclic loading 29–31 . Trans‐tunnel (i.e., RigidFix cross pins) could avoid eccentric fixation and graft injury caused by interference screws, also avoiding the “bungee effect” and “windshield wiper effect” caused by suspensory fixation, which is conducive to graft‐bone incorporation.…”
Section: Discussionmentioning
confidence: 99%
“…28 Suspensory fixation allows for circumferential tendon-bone contact, but its fixation point far away from the joint line can produce a "bungee effect" and a "windshield wiper effect" with cyclic loading. [29][30][31] Transtunnel (i.e., RigidFix cross pins) could avoid eccentric fixation and graft injury caused by interference screws, also avoiding the "bungee effect" and "windshield wiper effect" caused by suspensory fixation, which is conducive to graftbone incorporation. Thus, the trans-tunnel method seems to have advantages over the other two in theory.…”
Section: Graft Fixation Stylementioning
confidence: 99%
“…After ensuring that all intra-articular structures were intact, an ACL resection and anatomic single-bundle ACL-R were performed arthroscopically. 10,27,30,43 The ACL was transected using a punch and motorized shaver. The femoral tunnel was drilled in the center of the ACL footprint using a 10-mm cannulated femoral drill (Acufex; Smith & Nephew Inc) via the transportal technique.…”
Section: Methodsmentioning
confidence: 99%